Caracterização da fertilidade de cinco latossolos sob vegetação de Cerrado, no Triângulo Mineiro - Martins, Osvaldir; Braga, José Mário (Revista Ceres, 2025)
In order to characterize the fertility of soils from the cerrado of the Triângulo Mineiro by the missing element technique, trials were carried out in greenhouse of the Federal University of Viçosa, Viçosa, Minas Gerais, Brazil. Five soil samples were tested-two of dark red distrophic latosols (LEd] and LEdg), a purple distrophic latosol (LRd), red-yellow latosol (LVd) and a dark red latosol (LEm). Fifteen treatments were employed, one in which all the essential nutrients (nitrogen, phosphorus, potas- sium, calcium, magnesium, manganese, copper, iron, boron, molybdenum and zinc) plus cobalt were supplied. and the rest with one of these elements omitted. The soybean variety ‘UFV-1" was the test plant.